Influence of technological parameters of stabilization column operation (a part of diesel fuel production unit) on the content of hydrogen sulphide in stable gasoline; Проблемы геологии и освоения недр; Т. 2 - Zyryanova I. V. (Геология, горное и нефтегазовое дело (доклады на английском и немецком языках), 2016)
Заглавие с экрана